Mutation of the glucagon receptor gene and diabetes mellitus in the UK: association or founder effect? - Gough, S; Saker, P; Pritchard, L; Merriman, T; Merriman, M; Rowe, B; Kumar, S; Aitman, T; Barnett, A; Turner, R (1995)
Recent evidence suggests that a mutation of the glucagon receptor (GCG-R) gene is involved in the development of type 2 diabetes in French patients. We have examined patients from three geographically distinct regions in the UK and found the GGT40 (Gly) to AGT40 (Ser) mutation to be present in 15/691 (2.2%) of patients with type 2 (non-insulin dependent) diabetes and 1/425 (0.2%) of geographically matched controls and have therefore replicated association of the GCG-R mutation with classical type 2 diabetes (Fisher's exact test p = 0.008). An increased frequency of the mutation of the GCG-R gene was also found in probands of type 1 (insulin dependent) diabetic multiplex (affected sib pair) families, (10/404, 2.5%). However, a lack of preferential transmission from parents heterozygous for the mutation, to affected type 1 diabetic sibs may suggest population stratification. This in turn cannot be excluded as an alternative explanation for the difference in frequency of the GCG-R gene mutation between subjects with type 2 diabetes and normal controls.